A Moderation Analysis: How Did Financial Knowledge Influence Financial Management Behavior Madura Entrepreunerwomen Gen Y-Z - rohmah, yusriyatur; Susetyo, Achmad Budi; Hasan, Dony Burhan Noor (Universitas Kadiri, 2025)
MSMEs are a key component supporting national economic growth. This sector has a significant contribution to strengthening the national economy because it is able to reduce unemployment rates by creating new jobs for local communities. MSMEs also contribute significantly to economic growth, including in the Madura region, which shows a rapid increase in the number of MSMEs. However, along with this growth, MSMEs face various challenges, particularly related to financial management behavior. The expertise in manage finances is a crucial aspect in maintaining the persistence of SMEs. With good financial mastery, an entrepreneur can organize and allocate their financial resources effectively and on target. This study aims to analyze the influence of financial knowledge to financial management behavior between generations Y- Z in the Madura region. This study uses a quantitative approach, through questionnaires to gather primary data. literature studies, and interviews. The sample size was determined using the Lemeshow technique. Data analysis in this study was carried through the Structural Equation Modeling (SEM) approach applying Smart PLS software version 4.0.9.9. The study findings indicate that financial literacy exerts a favorable influence on financial management. However, Islamic financial literacy does not show a significant infuluence to financial management